Meme Politik di Era Digital: Dilema Kebebasan Ekspresi dan Penegakan Hukum dalam Negara Demokratis Pancasila - Maulana Muhamad, Randi; Faizin, Muhammad; Agus Pranata, Yuda; Afrizal, Mohamad (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study explores the tension between freedom of expression and the enforcement of criminal law in the digital space, using a case study of political memes depicting national figures Prabowo Subianto and Joko Widodo in a satirical context. The case sparked controversy after law enforcement authorities applied morality provisions from Indonesia's Electronic Information and Transactions Law (UU ITE), which many experts consider irrelevant to the substance of the content. Employing a qualitative approach through literature review, the analysis is framed within three theoretical perspectives: Constitutional Democracy Theory, Human Rights Theory, and Criminal Law Theory. The findings reveal that the application of ambiguous provisions in the UU ITE to digital expression has the potential to violate the rule of law, restrict civil liberties, and create a chilling effect on citizens' political participation. Consequently, this study recommends legal reform and the enhancement of digital literacy as strategies to strengthen constitutional democracy in the digital era.